Image Reconstruction in Optical Interferometry. Issue 69 (10th September 2015) - Young, J.; Thiébaut, E.
Abstract : This tutorial paper describes the problem of image reconstruction from interferometric data with a particular focus on the specific problems encountered at optical (visible/IR) wavelengths. The challenging issues in image reconstruction from interferometric data are introduced in the context of a general inverse problem approach. This framework is then used to describe state-of-the-art image reconstruction algorithms specifically developed for optical interferometry.